High-Resolution Peat Core Chronology Covering the Last 12 KYR Applying an Improved Peat Bog Sampling. Issue 5 (19th November 2018) - Hubay, Katalin; Braun, Mihály; Harangi, Sándor; Palcsu, László; Túri, Marianna; Jull, A J Timothy; Molnár, Mihály
ABSTRACT: This work focuses on building a high-resolution age-depth model for quantitative palaeoclimate study from the Mohos peat bog, East Carpathian mountains. The investigated core presents a continuous peat profile for the last 12 kyr. The chronology was based on 36 accelerator mass spectrometry radiocarbon (AMS 14 C) analyses of the separated Sphagnum samples from different depths of the profile. Dry Sphagnum samples for AMS dating were prepared using the classic acid-base-acid (ABA) method followed with an oxidative bleaching step to get clean cellulose. Sphagnum cellulose samples were measured by AMS using the EnvironMICADAS at the ICER (Debrecen, Hungary). A high-resolution chronology was obtained with the use of Bayesian age-depth modeling. Peat accumulation rate has been calculated and the sections with variable accumulation rate values were observed along the profile.